Structure of the glycosylphosphatidylinositol anchor of an arabinogalactan protein from Pyrus communis suspension-cultured cells - Oxley, David (The National Academy of Sciences, 1999)
Arabinogalactan proteins (AGPs) are proteoglycans of higher plants, which are implicated in growth and development. We recently have shown that two AGPs, NaAGP1 (from Nicotiana alata styles) and PcAGP1 (from Pyrus communis cell suspension culture), are modified by the addition of a glycosylphosphatidylinositol (GPI) anchor. However, paradoxically, both AGPs were buffer soluble rather than membrane associated. We now show that pear suspension cultured cells also contain membrane-bound GPI-anchored AGPs. This GPI anchor has the minimal core oligosaccharide structure, d-Manα(1–2)-d-Manα(1–6)-d-Manα(1–4)-d-GlcN-inositol, which is consistent with those found in animals, protozoa, and yeast, but with a partial β(1–4)-galactosyl substitution of the 6-linked Man residue, and has a phosphoceramide lipid composed primarily of phytosphingosine and tetracosanoic acid. The secreted form of PcAGP1 contains a truncated GPI lacking the phosphoceramide moiety, suggesting that it is released from the membrane by the action of a phospholipase D. The implications of these findings are discussed in relation to the potential mechanisms by which GPI-anchored AGPs may be involved in signal transduction pathways.